Utilização da tecnologia na formação dos professores de Matemática da região norte do Brasil - Pacheco, Edevaldo Gomes (Universidade Federal do Tocantins, 2021)
In the current educational context, there are new challenges, one of which comes from the learning problems that are related to traditional ways of teach mathematics. Thus, it is necessary that the teacher and the school, as well as the State, always seek to update themselves in relation to the new tools available to assist the learning process. The general objective of this work is to analyze how universities and institutes in the Northern region of Brazil have incorporated the use of technology in education, in the face-to-face courses of licensing in Mathematics, showing the importance of technology in education and exemplifying with some of its possible uses in the math classes. The public institutions selected for the research are those that offer the face-to-face course. This choice was based on the assumption of the influence of the State Education Plans of which they are a part, which has been proven. The data were collected in an exploratory way, through the MEC website, which has the register of all universities present in each State, and the research was of a documental character, through the Pedagogical Projects of the courses of licensing in Mathematics of each selected institution. A preponderant factor for a university to obtain positive results in relation to its approach to technologies in teaching, was the division of the workload between theoretical and practical and, in this sense, the universities of Pará were highlighted: UFOPA and UFPA, and, in the state of Tocantins, the UFT.